Attributive Compounds in the English and Armenian Languages - KARAPETYAN, SIRARPI (Bulletin of Yerevan University B: Philology, 2021)
The aim of the article is to study of one of the forms of subordinative compounds, i.e. compounds (synthetic constructions) syntactically characterized as attributive compounds (with the syntactic connection of “defining-defined”). The aim of the article is to reveal the differences and similarities of these compounds in both languages, analyze the components from morphological-categorial (to which part of speech they belong) point of view and of the syntactic connection between the components. Besides, the semantic fields of the first components of the compounds of this type are also studied. The observed peculiarities have great importance for the structural and typological characteristics of the languages being studied.